MIKROFASIES DAN DIAGENESIS BATUGAMPING BERDASARKAN DATA PETROGRAFI PADA FORMASI NAKFUNU DI DAERAH TIMOR TENGAH SELATAN - Sigit Maryanto; Asep Kurnia Permana (Jurnal Geologi dan Sumberdaya Mineral, 2013)
Microfacies and diagenesis of limestones from the Nakfunu Formation have been studied to tracing the depositional mechanism and post depositional geological histories of the rocks. Limestone samples randomly taken from the field on the Cretaceous rock formation, for petrographic analysis. Petrogrtaphic analysis of the fourty two limestone samples showing that the type of the limestones are packstone, wackestone, and mudstone. The depositional environments of this formation are include basin margin, open sea shelf near the lower slope, and deep sea basin with slow sedimentation. The limestones have affected by various kinds of diagenetic proccesses post-sedimentation. The diagenetic procceses recorded under the polarization microscope as: cementation, replacement, silicification, recrystallization, dolomitization, compaction, fracturing, and dissolution.Keywords: Cretaceous, limestone, petrography, microfacies, diagenesis.